The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0301006619899574
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects in the Recognition of Blurry Faces

Abstract: Spatial frequencies critical for recognition of faces are scale-dependent. Progressively coarser features of the face are utilized at smaller sizes, despite the availability of finer features. Blur removes fine details in an image, disrupting the finer features utilized for recognition at large sizes. At smaller sizes, observers utilize coarser features, and thus, recognition may be less impacted by blur. This coupling between size and critical spatial frequencies allows us to predict a regime in which observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Since it has been reported that different brain regions respond to the perception of beauty and ugliness (Nakamura & Kawabata, 2015), future research on the relationship between the rating results observed in psychophysical experiments and brain re sponses is recommended. Finally, the size of the presented face image may also affect blur processing (Mousavi & Oruc, 2020), thus experiments that consider these factors are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been reported that different brain regions respond to the perception of beauty and ugliness (Nakamura & Kawabata, 2015), future research on the relationship between the rating results observed in psychophysical experiments and brain re sponses is recommended. Finally, the size of the presented face image may also affect blur processing (Mousavi & Oruc, 2020), thus experiments that consider these factors are needed.…”
Section: Discussionmentioning
confidence: 99%
“…What are the best approaches to recognizing severely blurry faces? Coarser features are sufficient for supporting recognition of faces under some conditions, e.g., when they mimic viewing at a distance (Mousavi & Oruc, 2019;Oruc & Barton, 2010a;Shahangian & Oruc, 2014). Can we extrapolate from those conditions to help devise visual aids for people with blurry vision?…”
mentioning
confidence: 99%